Taxonomic review of Hadromerida (Porifera, Demospongiae) from British Columbia, Canada, and adjacent waters, with the description of nine new species - Austin, William C.; Ott, Bruce S.; Reiswig, Henry M.; Romagosa, Paula; Mcdaniel, Neil G. (Zootaxa, 2014)
The history of sponge collecting and systematics in British Columbia is reviewed over the period 1878 to 1966. Recent additions and changes are provided in an on-line species list: www.mareco/org/kml/projects/NEsponges.asp. Hadromerids are the focus of this paper as eight of 19 species in British Columbia are considered new. An additional new species is described from southern California to clarify the status of Tethya californiana in BC. An update is timely for hadromerids in BC as there is new material and renewed interest, while existing descriptions are often inadequate. We describe new species and provide additions to previous descriptions for sponges of the order Hadromerida (Porifera: Demospongiae) in the cold temperate NE Pacific off British Columbia and adjacent waters. We propose one range extension and one new species in Clionaidae; two range extensions and five new species in Polymastiidae; one range extension, two name changes and two new species in Suberitidae; and one new species in Tethyidae. New species include Pione gibraltarensis n.sp., Polymastia piscesae n. sp., Radiella endeavourensis n. sp., Sphaerotylus raphidophora n. sp., Sphaerotylus verenae n. sp., Weberella perlucida n. sp., Prosuberites saanichensis n. sp., Suberites lambei n. sp., and Tethya vacua n. sp..